Saturation transfer difference NMR on the integral trimeric membrane transport protein GltPh determines cooperative substrate binding - Hall, Jenny L. (Sci Rep, 2020)
Saturation-transfer difference (STD) NMR spectroscopy is a fast and versatile method which can be applied for drug-screening purposes, allowing the determination of essential ligand binding affinities (K(D)). Although widely employed to study soluble proteins, its use remains negligible for membrane proteins. Here the use of STD NMR for K(D) determination is demonstrated for two competing substrates with very different binding affinities (low nanomolar to millimolar) for an integral membrane transport protein in both detergent-solubilised micelles and reconstituted proteoliposomes. GltPh, a homotrimeric aspartate transporter from Pyrococcus horikoshii, is an archaeal homolog of mammalian membrane transport proteins—known as excitatory amino acid transporters (EAATs). They are found within the central nervous system and are responsible for fast uptake of the neurotransmitter glutamate, essential for neuronal function. Differences in both K(D)’s and cooperativity are observed between detergent micelles and proteoliposomes, the physiological implications of which are discussed.